Public financial management systems Myanmar key elements from a financial management perspective. (Asian Development Bank, 2020)
This report documents Myanmars financial management systems, covering primarily the areas of budgeting, funds flow, accounting and reporting, and auditing systems.It provides insights into the quality of internal control systems, staffing resource capacity, and information technology structure. The report aims to provide enhanced insights to stakeholders on financial management systems with the objective of improving the quality of financial management assessments during project preparation. High-quality financial management assessments support project implementation by identifying key fiduciary risks as well as appropriate actions and reforms to mitigate them.